Mills' and other isolated upper motor neurone syndromes: in vivo study with 11C-(R)-PK11195 PET. Issue 6 (16th May 2005) - Turner, M R; Gerhard, A; Al-Chalabi, A; Shaw, C E; Hughes, R A C; Banati, R B; Brooks, D J; Leigh, P N
Abstract : 11 C-(R)-PK11195 positron emission tomography (PET) was used to explore and delineate in vivo the cortical lesion in three clinically isolated upper motor neurone syndromes of similar presentation, with reference to the syndrome of progressive spastic hemiparesis first described by Mills. Three patients with isolated UMN syndromes underwent 11 C-(R)-PK11195 PET of the brain. One patient fulfilled criteria for PLS. Two others had clinical features similar to the cases described by Mills; one of these had a high cervical cord inflammatory lesion previously noted on magnetic resonance imaging. The patient with PLS showed focal increase in the binding of 11 C-(R)-PK11195, indicating microglial activation, in the motor cortex contralateral to the predominantly affected limbs. Of the other two patients, one demonstrated marked increases in binding in the superior frontal region (supplementary motor region) contralateral to the affected limbs. In contrast, no focal areas of increased binding were seen in the cerebral cortex of the third patient, who had a high cervical cord lesion and was presumed to have extra-cerebral inflammatory disease. 11 C-(R)-PK11195 PET demonstrates in vivo that active pathology may be detectable many years after the onset of symptoms, and that it can occur in disparate sites with clinically similar presentations. We conclude that Mills' syndrome is a purely clinical description that should be reserved for patients with a progressive spastic hemiparesis for which no other explanation can be found.